Whose team am i on anyway? Musings of a public defender about drug treatment court practice - Mae C. Quinn (My University, 2016)
This article seeks to contribute to drug treatment court discourse by analyzing drug treatment court practices from the perspective of a criminal defense attorney practicing within one such court. It outlines the methods through which these programs modify the traditional litigation-based playing field, introducing closer judicial supervision of criminal defendants in less adversarial settings.